Ecological structure of plant, insect and bird biodiversity and approaches to increasing the rationality of organic farming management (the case of Ukraine) - Miroshnyk, Nataliia; Grabovska, Tetiana; Lavrov, Vitaliy; Shupova, Tatiana; Grabovskyi , Mykola; Ternovyi, Yuriy; Roubík, Hynek; Prysiazhniuk , Nataliia (Ecological Questions, 2025)
The reduction of pesticides through organic farming releases some agricultural pest species from human control. We propose that this results in higher pest populations and indirectly, via plant diversity, affects avian community structure in agricultural landscapes. Therefore, we collected data on vegetation diversity (trees, bushes, herbs), from organic agrolandscapes and analyzed how vegetation diversity impacted the diversity and structure of insects and birds. The aim of this research is: i) To investigate the ecological, taxonomic, and functional structure of biodiversity in organic agricultural landscapes and its impact on ecosystem services. ii) To propose mechanisms for managing bird population in organic agro-ecosystems, considering biotic and transabiotic links. We used botanical, forestry and ecological methods to assess biodiversity. We found that plant diversity increases and species dominance decreases in ecotones approaching forest belts, insect diversity depends on the crop planted in fields, and bird diversity depends on landscape connectivity and structure. Fourteen families of insects occurred in the winter wheat field, 22 families in the buckwheat field, and 15 families in the soybean field. Among these, phytophages (40-69%) dominated, parasitic species ranged from 18 to 24%, and predators accounted for 7-26% of the total number of individuals collected. Twenty-eight bird species (6 food specialists) fed in the fields, dominated by species with broad diets. The list of species feeding in an area depended on the qualitative characteristics of the forest belt surrounding the area. We conclude that birds can serve as a practical pest control if combined with additional organic farming economic and environmental management strategies. To preserve biodiversity, it is important to take into account the structure of the forest shelterbelts, types of habitats due to the expansion of fields’ margins (ecotones), plants that resistant to damage by phytophagous insects, as well as tree species that can attract birds as a food base. Results on existing environmental risks and ways to mitigate them in organic farming can be used for systemic analyses of biodiversity structure in agro-landscapes: fields, their margins, forest shelterbelts, etc.